DAMPAK VIRUS CORONA (COVID-19) TERHADAP KEHIDUPAN SOSIAL BUDAYA MASYRAKAT HINDU BALI (PERSPEKTIF PENDIDIKAN AGAMA HINDU) - I Ketut Agus Murdiana (UHN I Gusti Bagus Sugriwa Denpasar, 2021)
The Coronavirus (Covid -19) has been declared a Pandemic by the World Health Organization or what is called the World Health Organizer (WHO), because it has spread to almost all countries in the world. Efforts to contain the spread of this virus are continuously being carried out, but in implementation it is inevitable that new impacts or problems will arise in the adjustment. For this reason, further research is needed in order to reveal the impacts arising from the adjustment of people's lives to the epidemic disaster management efforts. In this study, the research location was carried out in Bali. The approach in this study is a descriptive qualitative approach, which will explain the picture of the socio-cultural life of the Balinese Hindu community in the midst of the Covid -19 Pandemic. This study aims to determine the effects of the Covid-19 Pandemic so that it can be used as learning in the future to face similar disasters. The effects of this Pandemic are also studied from the perspective of Hindu religious education. As a result of the arrival of the Coronavirus (Covid -19), many significant changes have occurred in Bali. The results showed that the socio-cultural life of the Balinese people followed new adjustments or adaptations to anticipate the development of the Corona virus disease (Covid -19) outbreak. These adjustments include regulations, religious activities (regarding traditions) and social activities